Kecepatan Pelepasan Parasetamol dari Crosslinked Carrageenan-PVA Film: Pengaruh Rasio Carrageenan-PVA dan Waktu Pengisian (Loading) - Sri Sutriyani; Rieke Ulfha Noviyanti; Sperisa Distantina (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Carrageenan which was extracted from seaweed Eucheuma cottonii was mixed with polyvinylalcohol (PVA) andthen carrageenan-PVA was modified with crosslinking method using glutaraldehyde. The result of hydrogelfilms was applied to control the drug release rate of paracetamol. The aim of this research to determine amathematical model that can be used to describe the events of drug release paracetamol, determine the effect ofweight ratio carrageenan-PVA (5:0, 1:0.5, 1:1, 1:2, 0:5) and the loading time of paracetamol (2 and 12 hours)on the parameters of paracetamol release rate from carrageenan-PVA film in a buffer solution pH = 7,4. Theresearch include several steps, the step of making carrageenan-PVA films, crosslinking carrageenan-PVA films,filling the film with paracetamol (Loading) and releasing test of paracetamol in a buffer solution. Themathematical model arranged can describe the mass transfer rate of paracetamol. The weight ratio ofcarrageenan-PVA greatly affect the amount of paracetamol was absorbed in the hydrogel film (Xo) and therelease rate of paracetamol in a buffer solution (kCa). The longer time of loading, paracetamol could beadsorbed more. Paracetamol release rate was faster at loading time 12 hours compared to 2 hours except thePVA film without carrageenan.